PROJECT MANAGER LEADERSHIP STYLE WHICH INCREASES THE PROJECT PERFORMANCE - Lukiyanto, Kukuh (Journal of Sustainable Technology and Applied Science (JSTAS), 2023)
Maximum performance to achieve the specified target is the expectation of each project work. Leadership is one of the factors causing the achievement of good project performance. The purpose of this study is to find out what kind of project manager leadership style can improve the performance of all elements in the road project. This study uses qualitative methods to study the impact of leadership style on the success of road construction projects. Taking the object of research in East Java with 15 informants, in-depth interviews and observations were carried out for 6 months. Based on the analysis of the data obtained, a guiding leadership style, and open to discussion, can improve the performance of road construction projects.